A Study of the Lao Language Phonetic System of Villagers at Vangpa Village, Kaenthao District, Xayyabuly Province: https://doi.org/10.69692/SUJMRD0802158 - Bountavong, Sonesanith; Oukhamla, Chay; Noyvongthong , khammonh; Sisavhat, Thayna (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this research was to study the consonant and vowel sound system of Villagers at Vangpa Village, Kaenthao District, Xayyabuly Province. The sample consisted of 15 villagers who are living inVangpa Village. The researcher analyzed data using theory of OnKeo NUANNAVONG. The findings of this research were as follows: Consonant sound of villagers at Vangpa Village consisted of 19 sound units such as: ກ /k/, ຂ-ຄ /kh/, ຫງ-ງ /ŋ/, ຈ /c/, ສ-ຊ /s/, ຫຍ-ຍ /ɲ/, ດ /d/, ຕ /t/, ຖ-ທ /th/, ໜ-ນ /n/, ບ /b/, ປ /p/, ຝ-ຟ /f/, ໝ-ມ /m/, ຢ /j/, ຫຼ-ລ /l/, ຫວ-ວ /w/, ອ /ʔ/, ຫ-ຮ /h/ of which 19 sound units are the first letter of the syllable and 8 units are the last letter of the syllable. There are 2 sound units out of official consonant sound such as ຜ-ພ /ph/ because of villagers at Vangpa Village produce sound ຖ-ທ /th/. And villagers are not produce complex consonant sound of “ວ”. Vowel sound of villagers at Vangpa Village consisted of 22 sound units. Common vowels are 18 sound unit such as xະ /a/, xາ /a:/, xິ /i/, xີ /i:/, xຶ /ɯ/, xື /ɯ:/, xຸ /u/, xູ /u:/, ເxະ /е/, ເx /е:/, ແxະ /ɛ/, ແx /ɛ:/, ໂxະ /o/, ໂx /o:/, ເxາະ /ɔ/, xໍ /ɔ:/, ເອິ /ə/, ເອີ /ə:/. Diphthong sound of Villagers at vangpa village consisted of 4 sound units as ເອັຍ /ia/, ເອຍ /i: a/, ອົວະ /ua/, ອົວ /u: a/. There are not 2 sound units of official language as ເxຶອ /ɯa/, ເxືອ /:a/ because of Vangpa’s villagers produce sound of ເxັຍ /ia/, ເxຍ /i:a/. There are 3 special vowels of Vangpa’s villagers which are ໄx /aj/, ເxົາ/aw/, xຳ /am/. Vangppa’s villagers are not able to produce the sound ໃx. Instead, they produce sound ໄx.